Mob Programming for writing code with high complexity and remote work - Kattan, Herez Moise (2023)
Nowadays, the world relies on software, and the citizens of this modern world demand good quality software. Moreover, their needs change constantly. Hence, they require new software or new versions of existing ones that correctly solve their problems. Additionally, software development is not just about the cost or quality of software but also about the people who work to produce software. The motivation is to find better ways to organize the work of the programmers to develop quality software in a productive way suitable to their current context. The COVID-19 pandemic impacts the work environment and obligates people to work remotely. Furthermore, the software developed is increasingly complex. Thus, it emerges in society\'s need for software development techniques to create complex software with quality and permit software developers to work remotely. Creating reliable, stable, easy maintenance software is to its quality. This research is about an emerging, popular, and current practice to increase the quality of software development, learning, and programmer satisfaction: Mob Programming. The idea of Mob Programming is the entire team developing software as a group together around a computer and not as an isolated task. The research strategy is a Grounded Theory about Mob Programming. It is observed in practice its benefits in high complexity software development and remote work. Interviews, questionnaires, observations, and source code analysis produce raw data about these observations. Thence is analyzed these data using open code, constant comparison method, core category, selective coding, memoing, sorting, and theoretical coding following the Grounded Theory research method to serve as a recommendation for software developers with suggestions about team roles and practices related to how to use Mob Programming on complex tasks and remote work.